Speaker classification optimization design by vector quantization decision rule - Loh, Mun Yee, 1984-, author; Abdul Manan Ahmad, author; Fatimah Mohamad, author; International Conference on Information & Communication Technology Systems (4th: 2008: Indonesia) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL